2008
DOI: 10.1123/jsr.17.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Warm-Up Periods on Knee Proprioception and Balance in Healthy Young Individuals

Abstract: Both warm-up periods have positive effects on knee proprioception and balance. The 10-minute warm-up exercise improved proprioception by a greater amount than the 5 minutes warm-up exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 24 publications
3
30
0
2
Order By: Relevance
“…Although the observed positive eff ects could be due to changes in the conduction velocity [9,13] and / or joint position sense [3,5,37] improved by a single session of exercise as mentioned in the Introduction, we cannot determine the physiological mechanisms that are directly related to the improvement of postural stability nor the COP measures in the current experimental setup. Further studies should be conducted to clarify this point.…”
Section: ▼ Eff Ect Of a Single Session Of Exercise On Postural Stabilitymentioning
confidence: 62%
See 1 more Smart Citation
“…Although the observed positive eff ects could be due to changes in the conduction velocity [9,13] and / or joint position sense [3,5,37] improved by a single session of exercise as mentioned in the Introduction, we cannot determine the physiological mechanisms that are directly related to the improvement of postural stability nor the COP measures in the current experimental setup. Further studies should be conducted to clarify this point.…”
Section: ▼ Eff Ect Of a Single Session Of Exercise On Postural Stabilitymentioning
confidence: 62%
“…The nerve conduction velocity can be increased by executing a single session of exercise due to an increase in the body temperature [9,13] . Moreover, it has been reported that the agedependent reduction in postural stability detected by the COP measures largely depends upon decreased joint position sense [19] , which could improve after a single session of exercise [3,5,37] . Thus, several lines of physiological evidence exist, indicating that a single session of exercise is capable of improving both the sensorimotor and the somatosensory systems, which in turn can improve the COP measures.…”
mentioning
confidence: 99%
“…No presente estudo, não foram observadas alterações significativas no equilíbrio nas condições realizadas. Num estudo semelhante realizado por Subasi et al 21 , investigou-se os efeitos agudos de cinco e 10 minutos de aquecimento na propriocepção do joelho e no equilíbrio, com os olhos abertos e fechados. Ao contrário do presente estudo, os autores encontraram efeitos positivos sobre as variáveis supracitadas.…”
Section: Discussionunclassified
“…Since proprioception plays a vital role in the conscious and unconscious sensations, automatic control of movement, and motor coordination, improving proprioception in the course of warm-up might reduce the risk of injury and improve movement accuracy (Thacker, et al, 2003). Notwithstanding, few studies (Bartlett & Warren, 2002;Bouet & Gahery, 2000;Magalhaes, et al, 2010;Subasi, Gelecek, & Aksakoglu, 2008) investigated the impact of warm-up exercises on proprioception (Table 3). Indeed, the theoretical relation between warm-up, proprioception and reduced risk of sport injuries seems to be clearly established, however few studies determined the effect of pre-participation warm-up exercise on proprioception in athletes (Bartlett & Warren, 2002;Magalhaes, et al, 2010).…”
Section: Pre-participation Warm-up Exercisementioning
confidence: 99%
“…The authors concluded that after a period of stretching and gentle exercise knee proprioception is improved, indicating an increase in sensitivity of proprioceptive mechanisms associated with the ligaments around the knee. More recently, Subasi et al (2008) designed a study to determine the effects of different warming up periods on passive knee joint position sense of 30 healthy subjects. The 30 subjects were randomly distributed into a control (n = 10) and two exercise (each with n = 10) groups, which performed warmup exercises of different lengths (5 and 10 minutes).…”
Section: Pre-participation Warm-up Exercisementioning
confidence: 99%